The Effect of Auditor Reputation, Audit Fees, and Audit Tenure on Audit Delay, with Financial Distress as a Moderating Variable, in Manufacturing Companies Listed on the Indonesia Stock Exchange - Ego Salman; Afrizal Afrizal; Fitrini Mansur (Dhana, 2026)
This study aims to examine the effect of auditor reputation, audit fees, and audit tenure on audit delay with financial distress as a moderator. The sample consists of 99 manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2023–2025 period, with a total of 297 observations after removing 9 outliers. The analysis used Partial Least Square (PLS) with SmartPLS 4.0. The results show that auditor reputation, audit fees, and audit tenure have a significant negative effect on audit delay. Big 4 accounting firms complete audits 11.2 days faster, a 1-unit increase in Ln_Fee decreases the delay by 6.8 days, and an additional 1-year tenure decreases the delay by 2.1 days. Financial distress, proxied by the Altman Z-Score, is proven to moderate these three relationships. The advantages of Big 4 firms, high fees, and long tenure are greater in healthy companies and weaken in distressed companies because auditors become more conservative. The model has R² = 0.486, Q² = 0.461, and SRMR = 0.051. Practical implications: Regulators need to consider tiered deadlines for distressed issuers, public accounting firms need to implement risk-based pricing, and issuers should improve their financial health before turning to the Big 4.